Newly hired nurses' transitional challenges and coping with caring for schizophrenia patients in a psychiatric training hospital - Reynold Culimay Padagas; John Vinnie Panuelos; Kim Franco Odoya; Rhencel Cabardo; Vincent Pierre Louise Castro; Mary Ann Manio; Alexandrae Nabablit; Mikaela Angela Papilla (Tehran University of Medical Sciences, 2020)
Background & Aim: This study aimed to explore the transitional challenges of newly hired psychiatric nurses in the care of clients with schizophrenia and the coping mechanisms that they use to overcome their transitional challenges. Methods & Materials: This descriptive-qualitative study interviewed six purposively selected newly hired psychiatric nurses caring for patients with schizophrenia who work for about six months to two years in a Psychiatric Training Hospital in the Philippines.  An interview protocol was used to obtain data with strict observance of relevant ethical considerations. In determining the emerging themes and subthemes from the transcribed data with trustworthiness, thematic analysis was employed. Results: Two major prior codes were explored, namely, transitional challenges and coping mechanisms. On the one hand, five subthemes emerged under the transitional challenges that include emotional challenges, need for professional growth, nurses' recognition of the inability to patient care management, need support from more experienced colleagues. Experience/feel the shock in the encounter of people with a mental health condition. On the other hand, four subthemes were unearthed under coping mechanisms that include emotional responses, professional coping strategies (i.e., reliance on the adequate support system, establishing the professional nurse-patient relationship, call to professional advancement, and commitment to evidence-based practice), and institutional coping strategies. Conclusion: While newly hired nurses experience tremendous transitional challenges, their coping mechanisms continuously emerge and develop. The nursing administration needs to foster sustainable mentoring and resilience programs essential in aiding newly hired nurses' adaptation and adjustment to the professional work environment.